Three-dimensional mesoporous carbon composite silicon carbon negative electrode material and preparation method and application thereof

By preparing three-dimensional mesoporous carbon composite silicon-carbon anode material, the support effect of the three-dimensional structure is used to alleviate the volume expansion of the silicon-based anode material during the charging and discharging process, the battery cycle performance and safety problems are solved, and higher charge and discharge efficiency and longer cycle life are achieved.

CN119650652AActive Publication Date: 2025-03-18TIANFU JIANGXI LAB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411860276.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing silicon-based anode materials will experience significant volume expansion during charging and discharging, resulting in damage to the electrode structure and the cycling performance and safety of the battery, hindering its commercialization process.

Method used

By preparing three-dimensional mesoporous carbon composite silicon-carbon negative electrode material, the support effect of the three-dimensional structure provides sufficient space for silicon particles to alleviate volume expansion and maintain the integrity and stability of the electrode structure.

Benefits of technology

This material improves the ion and molecular diffusion speed through multi-stage pore structure, enhances the charge and discharge efficiency and cycle life, solves the battery performance problems caused by volume expansion of silicon-based negative electrode materials, and promotes its commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650652A_ABST
    Figure CN119650652A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional mesoporous carbon composite silicon carbon negative electrode material as well as a preparation method and application thereof, and relates to the technical field of batteries. A preparation method of a three-dimensional mesoporous carbon composite silicon carbon negative electrode material comprises the following steps: respectively dissolving an additive 1 and an additive 2 in deionized water to obtain a solution A and a solution B, and adding the solution A into the solution B to obtain a solution C; dissolving an additive 3 in deionized water to obtain a solution D, and adding the solution C into the solution D to obtain a solution E; calcining at high temperature to obtain a template A; reacting to obtain a solution G; a template B is obtained; a sample is obtained; drying the carbonized sample to obtain a dried sample; and performing high-temperature activation on the dried sample in a carbon dioxide gas environment to obtain a three-dimensional mesoporous carbon material, and performing chemical vapor deposition to obtain the three-dimensional mesoporous carbon composite silicon carbon negative electrode material. According to the invention, the problem of obvious volume expansion of the silicon-based negative electrode material in the charging and discharging process is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, with the increasing global awareness of environmental protection and the transformation of energy structure, the electric vehicle industry has ushered in an unprecedented period of rapid development. This trend has put forward more stringent requirements on the performance of lithium-ion batteries, especially in terms of energy density, cycle stability and safety. As the core component of lithium-ion batteries, negative electrode materials play a decisive role in the overall performance of batteries.

[0003] Traditionally, graphite has been widely used as the negative electrode material for commercial lithium-ion batteries due to its stable chemical properties, good conductivity and relatively low cost. However, the theoretical specific capacity of graphite negative electrode is only 372mAh / g, which has gradually failed to meet the market demand for high-energy storage, especially in the context of pursuing long-range and lightweight electric vehicles. Finding and developing negative electrode materials with higher energy density has become a research hotspot in the industry.

[0004] Among many potential high-energy-density negative electrode materials, silicon-based materials are regarded as an ideal substitute for graphite due to their abundant natural reserves (the second most abundant element in the earth's crust) and extremely high theoretical specific capacity (up to 4200mAh / g), and have great commercial potential. However, silicon-based materials face a severe challenge in practical applications: they undergo significant volume expansion during the charge and discharge process, with an expansion rate of up to 300%. This volume effect not only causes the crushing and shedding of silicon active materials, destroying the integrity of the electrode structure, but also causes the repeated formation and rupture of the solid electrolyte interphase (SEI) film, accelerating the consumption of the electrolyte and the loss of Li+ ions, thereby seriously damaging the cycle performance and safety of the battery, and hindering the commercialization of silicon-based negative electrode materials.

[0005] Therefore, there is an urgent need to find a material that can alleviate the volume expansion of silicon during the cycle process in order to fully utilize the silicon-based negative electrode materials. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the existing silicon-based negative electrode materials will undergo significant volume expansion during the charging and discharging process, which hinders the commercialization process of silicon-based negative electrode materials. The purpose of the present invention is to provide a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material and its preparation method and application. By utilizing the supporting effect of the three-dimensional structure, sufficient space is provided for silicon particles to alleviate their volume expansion during the charging and discharging process, while maintaining the integrity and stability of the electrode structure, extending the cycle life of the battery, and promoting the commercial application of silicon-based negative electrode materials.

[0007] The present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material, comprising the following steps:

[0009] Dissolve additive 1 and additive 2 in deionized water respectively to obtain solution A and solution B. Add solution A to solution B under stirring to obtain solution C. Additive 1 is a silicon source material.

[0010] Additive 3 is dissolved in deionized water to obtain solution D. Solution C is added to solution D under stirring to obtain solution E;

[0011] The solution E is subjected to aging treatment, and then subjected to a hydrothermal reaction to obtain a reaction product;

[0012] The supernatant of the reaction product is discarded, the product is collected by centrifugation, dried, and calcined at high temperature to obtain template A;

[0013] Dissolving additive 4 in solvent 1 to obtain solution F;

[0014] Adding the carbon source solution dropwise to solution F to obtain solution G after reaction;

[0015] Solution G is infiltrated dropwise into template A, dried after stirring, and cured at high temperature to obtain template B;

[0016] The pore-forming agent and template B are added into deionized water and mixed evenly, and then dried to obtain a sample;

[0017] The sample was calcined under oxygen-free conditions to obtain a carbonized sample;

[0018] The carbonized sample is placed in solvent 2 and stirred to disperse, and then centrifuged to obtain a dry sample;

[0019] The dried sample is activated at high temperature in a carbon dioxide gas environment to obtain a three-dimensional mesoporous carbon material;

[0020] The three-dimensional mesoporous carbon material is subjected to chemical vapor deposition to obtain a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material.

[0021] As a possible design, the additive 1 is dissolved in deionized water by adding the additive 1 into deionized water, heating and stirring until it melts, and then adding hydrochloric acid to adjust the pH to 3-4 to obtain solution A; the additive 2 is dissolved in deionized water by repeatedly soaking and washing the additive 2 with hydrochloric acid, then washing the additive 2 with deionized water until the pH is 7, and adding deionized water to stir and melt to obtain solution B;

[0022] The additive 1 includes one or more of sodium silicate, ethyl orthosilicate and methyl orthosilicate; the additive 2 is a cation exchange resin.

[0023] As a possible design, the additive 3 is dissolved in deionized water by adding the additive 3 into deionized water, heating and stirring until it melts, and then adding hydrochloric acid to adjust the pH to 2-4 to obtain a solution D;

[0024] The additive 3 is hexadecyltrimethylammonium bromide.

[0025] As a possible design, the aging treatment of solution E is specifically to age solution E at 15-35° C. for 12-24 h.

[0026] As a possible design, the drying temperature of the reaction product is 60-80°C, and the drying time is 8-10h; the calcination temperature is 500-600°C, the calcination time is 5-6h, and the calcination heating rate is 2-5°C / min.

[0027] As a possible design, the above-mentioned dissolving the additive 4 in the solvent 1 specifically comprises dissolving the additive 4 in the solvent 1, stirring at room temperature until dissolved, and then adding hydrochloric acid to adjust the pH to 1-2 to obtain a solution F;

[0028] The additive 4 is a nonionic surfactant; the solvent 1 is an ethanol aqueous solution.

[0029] As a possible design, after the solution F is added with the carbon source solution, the mass ratio of the additive 4 to the carbon source is 1:(3-7); the carbon source includes one or more of phenolic resin, polyacrylonitrile and polydopamine;

[0030] The mass ratio of the pore-forming agent to the template B is 1:(1.8-2.2); the pore-forming agent includes one or more of sodium carbonate, urea, ammonium nitrate and zinc chloride;

[0031] The solvent 2 is a NaOH solution or a HF solution;

[0032] The high temperature activation is specifically activated at 750-850°C for 1-2h;

[0033] The three-dimensional mesoporous carbon material has an ant nest shape.

[0034] As a possible design, the chemical vapor deposition of the three-dimensional mesoporous carbon material specifically includes the following steps:

[0035] The three-dimensional mesoporous carbon material is evenly spread in a quartz boat, placed in the center of a chemical vapor deposition reaction chamber, and an inert gas is introduced to clean the reaction chamber;

[0036] A mixed gas 1 is introduced into a chemical vapor deposition reaction chamber to deposit a three-dimensional mesoporous carbon material, wherein the mixed gas 1 includes a silicon source gas;

[0037] A mixed gas 2 is introduced into the chemical vapor deposition reaction chamber to perform secondary deposition on the three-dimensional mesoporous carbon material, wherein the mixed gas 2 includes a carbon source gas;

[0038] The three-dimensional mesoporous carbon material after secondary deposition is placed in an inert gas for annealing treatment to obtain a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material.

[0039] In a second aspect, the present invention provides a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material, which is prepared by the above-mentioned preparation method.

[0040] In a third aspect, the present invention provides the application of the three-dimensional mesoporous carbon composite silicon-carbon negative electrode material prepared by the above preparation method in battery materials.

[0041] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0042] The carbon material with an ant nest-type three-dimensional mesoporous structure prepared by the present invention realizes the optimization of the multi-level pore structure, forming a three-dimensional network system of interconnected macropores and mesopores, which not only improves the specific surface area of ​​the material, but also significantly enhances the connectivity of the pores. The adjustable parameters in the preparation process make the pore size, pore distribution and structure controllable, enhance the application flexibility of the material and the controllability of the preparation process, and overcome the shortcomings of the traditional single template method in pore size regulation and pore connectivity. At the same time, the multi-level pore structure improves the diffusion rate of ions and molecules, so that the material has higher charge and discharge efficiency and longer cycle life in electrochemical devices such as lithium batteries. In addition, the three-dimensional network structure gives the material excellent mechanical strength and thermal stability, and can remain stable under high temperature or high pressure environments, solving the problem of easy collapse or deformation of traditional mesoporous carbon materials.

[0043] Specifically, the present invention forms mesoporous silica as a template for porous carbon by calcination, providing a basic framework for the preparation of porous carbon; by adding additives 4 and carbon sources, the material can be promoted to generate smaller voids, and combined with the effect of pore-forming agents, an ordered mesoporous structure is further formed in the macroporous structure, and the mesopores and macroporous structures are effectively connected to form a multi-level pore system. The combination of multiple treatments can greatly increase the specific surface area of ​​the material and form an ant nest type three-dimensional mesoporous structure. In the ant nest type structure, the pores often show the characteristics of small outlets and large pore volumes. Smaller pore outlets help reduce the escape of active materials such as silicon during the charge and discharge process. The advantage of this structure is that even if the material undergoes expansion or contraction (such as the volume change of the silicon negative electrode), the small pore outlet can still effectively limit the escape of the material, and the presence of macropores and mesopores can accommodate and support the expanded material. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0045] Figure 1 Schematic diagram of the cross section (left) and structural diagram (right) of the honeycomb structure of the three-dimensional mesoporous carbon composite silicon-carbon negative electrode material of the present invention. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0047] The existing silicon-based negative electrode materials will undergo significant volume expansion during the charging and discharging process, which hinders the commercialization of silicon-based negative electrode materials. In order to solve this problem, the present invention provides a method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material. By using a mesoporous carbon structure with high mechanical strength as a support, a three-dimensional network is constructed, and the volume expansion of silicon particles during the charging and discharging process is effectively limited through physical constraints. The special structure of mesoporous carbon not only gives the material excellent mechanical stability, but also provides a large specific surface area and suitable pore volume, which is beneficial to the penetration of electrolyte and Li + This technology not only solves the key problems of low cell cycle capacity and short cycle life caused by volume expansion of silicon-based negative electrode materials, but also opens up a new direction for the research and development of high-performance lithium-ion battery negative electrode materials.

[0048] A method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material comprises the following steps:

[0049] S1. Dissolve additive 1 and additive 2 in deionized water respectively to obtain solution A and solution B. Add solution A to solution B under stirring to obtain solution C. Additive 1 is a silicon source substance.

[0050] Preferably, the mass ratio of the additive 1 to deionized water is 1:(10-20), and the mass ratio of the additive 2 to deionized water is 1:(20-30).

[0051] Preferably, the volume ratio of the solution A to the solution B is 1:(1-1.5).

[0052] In some embodiments of the present invention, the above step S1 includes the following steps:

[0053] S101, adding additive 1 to deionized water, heating and stirring until melted, then adding hydrochloric acid to adjust the pH to 3-4 to obtain solution A.

[0054] S102, repeatedly soaking and washing the dispersed additive 2 with hydrochloric acid, then washing the additive 2 with deionized water until the pH value is 7, adding deionized water and stirring to melt to obtain a solution B.

[0055] Preferably, the melting temperature is 40-60°C, and the stirring speed is 20-60 rpm / min.

[0056] S103. While stirring, slowly add solution A to solution B, stir at room temperature (15-35° C.) for 1-2 h to avoid local coagulation, and obtain solution C.

[0057] In some embodiments of the present invention, the additive 1 includes one or more of sodium silicate, ethyl orthosilicate and methyl orthosilicate; the additive 2 is a cation exchange resin, preferably a hydrogen cation exchange resin (H+ type).

[0058] S2. Dissolve additive 3 in deionized water to obtain solution D. Add solution C to solution D under stirring to obtain solution E.

[0059] Preferably, the mass ratio of the additive 3 to deionized water is 1:(20-30).

[0060] Preferably, the volume ratio of the above solution C and solution D is 1:(1-1.5).

[0061] In some embodiments of the present invention, the above step S2 includes the following steps:

[0062] S201. Add additive 3 to deionized water, heat and stir until melted, then add hydrochloric acid to adjust the pH to 2-4 to obtain solution D.

[0063] Preferably, the heating temperature is 40-60° C., and the stirring speed is 20-60 rpm / min.

[0064] S202. While stirring, slowly drop solution C into solution D, stir at room temperature for 1-2 hours to avoid local coagulation, and obtain solution E.

[0065] In some embodiments of the present invention, the additive 3 is cetyltrimethylammonium bromide (CTAB).

[0066] S3, aging solution E, and then performing a hydrothermal reaction to obtain a reaction product.

[0067] In some embodiments of the present invention, the aging is specifically aging the solution E at room temperature (15-35° C.) for 12-24 hours.

[0068] Preferably, the hydrothermal reaction temperature is 100-120° C., and the hydrothermal time is 6-12 h.

[0069] S4. The supernatant of the reaction product is discarded, the product is collected by centrifugation, dried, and calcined at high temperature to obtain template A.

[0070] Specifically, mesoporous silica is formed as a template for porous carbon through calcination. Mesoporous silica is a hard material with large pore characteristics. Under high temperature conditions, these templates form a skeleton structure of carbon materials through carbonization or sintering, and this skeleton structure has excellent mechanical strength, providing a basic framework for the preparation of porous carbon.

[0071] In some embodiments of the present invention, the drying temperature of the reaction product is 60-80°C, and the drying time is 8-10h; the calcination temperature is 500-600°C, the calcination time is 5-6h, and the calcination heating rate is 2-5°C / min.

[0072] S5. Dissolve the additive 4 in the solvent 1 to obtain a solution F.

[0073] Preferably, the mass ratio of the additive 3 to the solvent 1 is 1:(10-14).

[0074] In some embodiments of the present invention, the above step S5 specifically comprises dissolving the additive 4 in the solvent 1, stirring at room temperature until dissolved, and then adding hydrochloric acid to adjust the pH to 1-2 to obtain a solution F.

[0075] Preferably, the additive 4 is a nonionic surfactant, preferably a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123). The addition of P123 and a carbon source can promote the material to generate smaller voids.

[0076] In some embodiments of the present invention, the solvent 1 is an ethanol aqueous solution.

[0077] Preferably, the mass ratio of water to ethanol in solvent 1 is (2.5-3.5): 1. More preferably, water: ethanol = 3:1.

[0078] S6. Add the carbon source solution dropwise to solution F to obtain solution G after reaction.

[0079] The addition of additive 4 and carbon source can promote the formation of smaller voids in the material, which is a key step in regulating the specific surface area and pore volume of the material.

[0080] Preferably, the above reaction is stirred at room temperature for 10-14 hours, preferably 12 hours.

[0081] In some embodiments of the present invention, the carbon source includes one or more of phenolic resin, polyacrylonitrile and polydopamine.

[0082] In some embodiments of the present invention, after the solution F is added to the carbon source solution, the mass ratio of the additive 4 to the carbon source is 1:(3-7).

[0083] The carbon source solution infiltrates and fills the pores of template A to form a uniform carbon skeleton structure. When the carbon sources infiltrate the pores of the template, they form a highly stable carbon skeleton after high-temperature curing. This carbon skeleton is enhanced during the subsequent high-temperature calcination process, thereby constructing the final three-dimensional mesoporous carbon structure. If the proportion of the carbon source is too high, it will lead to excessive carbon deposition, which may fill the pores of the template, making the pore structure incomplete or damaged, thereby reducing the specific surface area and pore volume of the final material; excessive carbon deposition may also cause pore blockage and affect the formation of a multi-level pore system. If the proportion of the carbon source is too low, it may not be possible to form enough carbon skeletons on the template, resulting in an incomplete porous structure or insufficient strength; too little carbon source will make the final carbon material have a low specific surface area and uneven pores, affecting the mechanical and electrochemical properties of the material. The ideal carbon source ratio should provide sufficient carbon deposition to form a stable skeleton while avoiding filling too many pores. The appropriate amount of carbon source can ensure that the pores of the template remain open and form a good three-dimensional mesoporous structure, thereby optimizing the specific surface area, pore volume and pore connectivity. P123: Carbon source = 1: (3-7), this range can usually obtain a more uniform and efficient multi-level pore structure.

[0084] S7, infiltrating solution G dropwise into template A, stirring and drying, and curing at high temperature to obtain template B.

[0085] Preferably, the mass ratio of the above solution G to the template A is (2-3):1.

[0086] Preferably, the stirring is carried out at room temperature for 10-14 hours, preferably 12 hours.

[0087] Preferably, the drying temperature is 60° C., and the drying time is 10-14 hours, preferably 12 hours.

[0088] Preferably, the high temperature curing temperature is 100-140° C., preferably 120° C.; the high temperature curing time is 4-6 hours.

[0089] S8. Add the pore-forming agent and template B into deionized water, mix well, and obtain a sample after drying.

[0090] Since template B itself can provide a structural framework and a certain pore size, but it cannot fully generate a complex pore network or fully optimize the distribution, connectivity and morphology of pores. Therefore, pore formers are still needed to further enrich and optimize the pore structure. Pore formers mainly generate pores in a high temperature process by chemical reaction or gas release, and these pores can refine and expand the existing pore network. The template mainly forms large and medium pores, and the number and morphology of pores may be limited. Adding pore formers can introduce small pores, further improve the density and diversity of pores, and form a multi-level pore structure. Pore formers can precisely adjust the formation of pores, and form pores of different shapes and sizes through gas release, chemical reaction, etc. The pores formed by the template are often relatively fixed in size and distribution, and cannot fully meet the requirements for pore diversity and uniformity. The addition of pore formers can supplement and refine these pores and optimize the morphology and distribution of pores.

[0091] Preferably, the mass ratio of the pore-forming agent to the template B is 1:(1-3).

[0092] Preferably, the above step S8 specifically includes adding the pore-forming agent and template B into deionized water and stirring for 12 hours to fully mix them, and then drying for 10-14 hours to obtain a sample. The drying time is preferably 12 hours.

[0093] In some embodiments of the present invention, the mass ratio of the pore-forming agent to the template B is 1:(1.8-2.2), preferably 1:2.

[0094] In some embodiments of the present invention, the pore-forming agent includes one or more of sodium carbonate, urea, ammonium nitrate and zinc chloride.

[0095] Preferably, the drying temperature is 80-100°C.

[0096] S9. calcining the sample under oxygen-free conditions to obtain a carbonized sample.

[0097] The above S9 specifically includes placing the sample in a tubular furnace and calcining it under an inert gas atmosphere to obtain a carbonized sample.

[0098] The calcination temperature is 800-1000°C, the heating rate is 5°C / min, and the calcination time is 2h; the inert gas is one or more of argon and nitrogen, and the gas flow rate is 1-5L / min.

[0099] S10, placing the carbonized sample in solvent 2, stirring and dispersing it, and obtaining a dry sample after centrifugal drying.

[0100] In some embodiments of the present invention, the solvent 2 is a NaOH solution or a HF solution.

[0101] Preferably, the solvent 2 is a 2M NaOH solution or a 5wt% HF solution; the stirring time is 10-14h, preferably 12h.

[0102] S11. Activate the dried sample at high temperature in a carbon dioxide gas environment to obtain a three-dimensional mesoporous carbon material.

[0103] Preferably, the high temperature activation is specifically activated at 750-850°C for 1-2 hours. Preferably, the activation temperature is 800°C.

[0104] In some embodiments of the present invention, the three-dimensional mesoporous carbon material is in an ant nest shape.

[0105] S12. Perform chemical vapor deposition (CVD) on the three-dimensional mesoporous carbon material to obtain a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material.

[0106] In some embodiments of the present invention, the above S12 includes the following steps:

[0107] S1201. Evenly spread the three-dimensional mesoporous carbon material in a quartz boat, place it in the center of a chemical vapor deposition reaction chamber, and introduce an inert gas to clean the reaction chamber.

[0108] Preferably, the inert gas is nitrogen and / or argon; the inert gas flow rate is 200 mL / min, and the cleaning time is 15-30 min.

[0109] S1202, introducing a mixed gas 1 into a chemical vapor deposition reaction chamber to perform a deposition on a three-dimensional mesoporous carbon material, wherein the mixed gas 1 includes a silicon source gas.

[0110] Preferably, the above-mentioned deposition is performed at 400-600° C. for 30-60 min.

[0111] Preferably, the mixed gas 1 comprises a silicon source gas and a carrier gas, wherein the silicon source gas comprises SiH4 and / or SiCl4; the carrier gas is nitrogen and / or argon. The silicon source gas flow rate is 10-20 mL / min; and the carrier gas flow rate is 200 mL / min.

[0112] S1203, introducing a mixed gas 2 into a chemical vapor deposition reaction chamber to perform secondary deposition on the three-dimensional mesoporous carbon material, wherein the mixed gas 2 includes a carbon source gas.

[0113] Preferably, the secondary deposition is performed at 700-900° C. for 30-60 min.

[0114] Preferably, the mixed gas 2 comprises a carbon source gas and a carrier gas, wherein the carbon source gas comprises C2H2, C2H4 and / or CH4. The carrier gas is nitrogen and / or argon. The carbon source gas flow rate is 10-20 mL / min; the carrier gas flow rate is 200 mL / min.

[0115] S1204, placing the three-dimensional mesoporous carbon material after the secondary deposition in an inert gas for annealing treatment to obtain a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material.

[0116] Preferably, the annealing temperature is 700-900° C., and the annealing time is 1-2 h.

[0117] The present invention also provides a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material, which is prepared by the above-mentioned preparation method.

[0118] The present invention also provides application of the three-dimensional mesoporous carbon composite silicon-carbon negative electrode material prepared by the above preparation method in battery materials.

[0119] Example 1

[0120] S1: Weigh 66.7g of additive 1 and add it to 1000g of deionized water, heat and stir until melted, then add hydrochloric acid to adjust the pH to 4 to obtain solution A; weigh 40g of additive 2, repeatedly soak and rinse with hydrochloric acid to disperse, then rinse with deionized water to pH = 7, add deionized water to melt to obtain solution B; under stirring, add 1000mL of solution A to 1200mL of solution B, slowly drop solution A into solution B, stir at room temperature for 2h to avoid local coagulation, and obtain solution C. Additive 1 is sodium silicate, additive 2 is cation exchange resin (H+ type), heating temperature is 50℃, and stirrer speed is 50rpm / min.

[0121] S2: Weigh 40g of additive 3 and add it to deionized water, heat and stir until it melts, then add hydrochloric acid to adjust the pH to 4 to obtain solution D; under stirring, add 1000mL of solution C to 1200mL of solution D, slowly drop solution C into solution D, stir at room temperature for 2h to avoid local coagulation, and obtain solution E. Additive 3 is hexadecyltrimethylammonium bromide (CTAB), the heating temperature is 60°C, and the stirrer speed is 50rpm / min.

[0122] S3: Solution E was aged at room temperature for 24 hours, and then transferred to a hydrothermal reactor for hydrothermal reaction at a reaction temperature of 120° C. and a hydrothermal time of 12 hours.

[0123] S4: The supernatant liquid of the above reaction product is discarded, and the product is collected by centrifugation and dried. The dried product is placed in a muffle furnace and calcined at high temperature to obtain template A. The drying temperature is 70°C, the drying time is 10 hours, the calcination temperature is 600°C, the calcination time is 6 hours, and the heating rate is 5°C / min.

[0124] S5: Weigh 83.3 g of an appropriate amount of additive 4 and dissolve it in 1000 g of solvent 1, stir at room temperature until dissolved, then add hydrochloric acid to adjust the pH to 2 to obtain solution F. Additive 4 is P123, the solvent is a mixture of water and ethanol, and the mass ratio of the solvent is water:ethanol = 3:1.

[0125] S6: Add the carbon source solution dropwise to solution F, and continue stirring at room temperature for 12 hours to obtain solution G. The carbon source is phenolic resin, and the mass ratio of solution is P123:carbon source=1:3.

[0126] S7: 250 g of solution G was dropwise infiltrated into 100 g of template A, and the mixture was stirred at room temperature for 12 h and then dried, and then cured at high temperature to obtain template B. The drying temperature was 60° C. and the drying time was 12 h; the curing temperature was 120° C. and the curing time was 6 h.

[0127] S8: 100 g of pore former (zinc chloride) and 200 g of template B were added into deionized water to dissolve and stir for 12 h to fully mix, and then dried for 12 h to obtain a sample. The pore former was zinc chloride, and the mass ratio was pore former: template B = 1:2. The drying temperature was 80°C.

[0128] S9: placing the above sample in a tube furnace and calcining it in an inert gas atmosphere to obtain a carbonized sample, wherein the calcination temperature is 1000°C, the heating rate is 5°C / min, the calcination time is 2h, and the inert gas is one of nitrogen, and the gas flow rate is 5L / min.

[0129] S10: The carbonized sample is placed in a solvent and stirred at room temperature for dispersion, and then centrifuged and dried to obtain a sample, wherein the solvent is 2M NaOH solution, and the stirring time is 12 hours.

[0130] S11: activating the sample at high temperature in a CO2 gas environment to obtain an ant nest type three-dimensional mesoporous carbon material, wherein the activation temperature is 800°C and the activation time is 2 hours.

[0131] S12: evenly spread the ant nest type three-dimensional mesoporous carbon material in a quartz boat, put it in the center of the CVD reaction chamber and introduce inert gas to clean the reaction chamber, wherein the inert gas is nitrogen, the gas flow rate is 200 mL / min, and the cleaning time is 30 min;

[0132] A mixed gas was introduced for high-temperature deposition, wherein the mixed gas was a silicon source gas (SiH4, gas flow rate was 20 mL / min) and a carrier gas (nitrogen, gas flow rate was 200 mL / min), the temperature was 600°C, and the deposition time was 60 minutes;

[0133] A mixed gas was introduced for high-temperature deposition, wherein the mixed gas was a carbon source gas (CH4, gas flow rate was 20 mL / min) and a carrier gas (nitrogen, gas flow rate was 200 mL / min), the temperature was 800°C, and the deposition time was 60 minutes;

[0134] The above samples were placed in an inert gas annealing treatment to obtain a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material (such as Figure 1 As shown), the inert gas is nitrogen, the annealing temperature is 800°C, and the annealing time is 2h.

[0135] Example 2

[0136] This embodiment is basically the same as Embodiment 1, except that the mass ratio of P123 to carbon source in S6 is 1:4, and other conditions are the same.

[0137] Embodiment 3:

[0138] This embodiment is basically the same as Embodiment 1, except that the mass ratio of P123 to carbon source in S6 is 1:5, and other conditions are the same.

[0139] Example 4

[0140] This embodiment is basically the same as Embodiment 1, except that the mass ratio of P123 to carbon source in S6 is 1:6, and other conditions are the same.

[0141] Example 5

[0142] This embodiment is basically the same as Embodiment 1, except that the mass ratio of P123 to carbon source in S6 is 1:7, and other conditions are the same.

[0143] Example 6

[0144] This embodiment is basically the same as Embodiment 1, except that the pore-forming agent in S8 is urea.

[0145] Example 7

[0146] This embodiment is basically the same as Embodiment 1, except that the pore-forming agent in S8 is ammonium nitrate.

[0147] Example 8

[0148] This embodiment is basically the same as embodiment 1, except that the carbon source in S6 is polydopamine.

[0149] Example 9

[0150] This embodiment is basically the same as Embodiment 1, except that: the amount of additive 1 in S1 is 100 g, the amount of additive 2 is 50 g, and the volume ratio of solution A and B is 1:1.5; the volume ratio of solution C and D in S2 is 1:1.5; the amount of additive 4 in S4 is 100 g; solution G: template A = 2:1 in S7; and pore former: template B = 1:3 in S8.

[0151] Comparative Example 1:

[0152] This comparative example is basically the same as Example 1, except that the mass ratio of P123 to carbon source in S6 is 1:5, the pore-forming treatment of S8 is not performed, and the other conditions are the same.

[0153] Comparative Example 2:

[0154] This comparative example is basically the same as Example 1, except that the mass ratio of P123 to carbon source in S6 is 1:6, the pore-forming treatment of S8 is not performed, and the other conditions are the same.

[0155] Comparative Example 3

[0156] This comparative example is basically the same as Example 1, except that the mass ratio of P123 to carbon source in S6 is 1:7, the pore-forming treatment of S8 is not performed, and the other conditions are the same.

[0157] Comparative Example 4

[0158] This comparative example is basically the same as Example 1, except that the mass ratio of P123 to carbon source in S6 is 1:2.

[0159] Comparative Example 5

[0160] This comparative example is basically the same as Example 1, except that the mass ratio of P123 to carbon source in S6 is 1:10.

[0161] Experimental Example 1

[0162] The three-dimensional mesoporous carbon composite silicon-carbon negative electrode material obtained in Examples 1-5 and Comparative Examples 1-3 was used to make a button half-cell, wherein the mass ratio of silicon-carbon, SP, CNT, CMC, and SBR was 92:2:2:1.5:2.5. The materials were mixed and stirred to form a slurry, which was coated on a copper foil current collector, and finally made into a CR2032 button cell for testing, with a test voltage window of 0.005-1.5V. The specific surface area, pore volume, gram capacity, and cycle performance of the battery were tested, and the results are shown in Table 1.

[0163] Table 1

[0164]

[0165] It can be seen from Table 1 that when the mass ratio of P123 to the carbon source is 1:5, the specific surface area, specific surface area, pore volume, gram capacity and cycle performance of the material are all the largest, so that the battery capacity density is good, the battery charge and discharge efficiency is high, and the battery service life is long. Comparing Example 1 and Comparative Examples 1-3, it can be seen that when the pore-forming agent is not used, even if the mass ratio of P123 to the carbon source is 1:5, the specific surface area will be reduced by nearly 500. This shows that the use of pore-forming agents and the mass ratio of P123 to the carbon source have a prominent effect on battery performance. Comparing Example 1 and Comparative Examples 4-5 again, when the mass ratio of P123 to the carbon source is 1:2, the specific surface area is reduced to 372.1, which shows that the small pores will affect the performance of the battery, resulting in poor charge and discharge efficiency and a shorter cycle life; when the ratio of the two is 1:10, the specific surface area is reduced to 306.2, which will also lead to poor charge and discharge efficiency and a shorter cycle life. It can be seen that the performance is best when the mass ratio of P123 to carbon source is =1:(3-7).

[0166] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material, characterized in that: The steps include: Dissolve additive 1 and additive 2 in deionized water respectively to obtain solution A and solution B. Add solution A to solution B under stirring to obtain solution C. Additive 1 is a silicon source material. Additive 3 is dissolved in deionized water to obtain solution D. Solution C is added to solution D under stirring to obtain solution E; The solution E is subjected to aging treatment, and then subjected to a hydrothermal reaction to obtain a reaction product; The supernatant of the reaction product is discarded, the product is collected by centrifugation, dried, and calcined at high temperature to obtain template A; Dissolving additive 4 in solvent 1 to obtain solution F; Adding the carbon source solution dropwise to solution F to obtain solution G after reaction; Solution G is infiltrated dropwise into template A, dried after stirring, and cured at high temperature to obtain template B; The pore-forming agent and template B are added into deionized water and mixed evenly, and then dried to obtain a sample; The sample was calcined under oxygen-free conditions to obtain a carbonized sample; The carbonized sample is placed in solvent 2 and stirred to disperse, and then centrifuged to obtain a dry sample; The dried sample is activated at high temperature in a carbon dioxide gas environment to obtain a three-dimensional mesoporous carbon material; The three-dimensional mesoporous carbon material is subjected to chemical vapor deposition to obtain a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material.

2. The method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material according to claim 1, characterized in that: The additive 1 is dissolved in deionized water by adding the additive 1 into deionized water, heating and stirring until it melts, and then adding hydrochloric acid to adjust the pH to 3-4 to obtain solution A; the additive 2 is dissolved in deionized water by repeatedly soaking and washing the additive 2 with hydrochloric acid, then washing the additive 2 with deionized water until the pH is 7, and adding deionized water to stir and melt to obtain solution B; The additive 1 includes one or more of sodium silicate, ethyl orthosilicate and methyl orthosilicate; the additive 2 is a cation exchange resin.

3. The method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material according to claim 1, characterized in that: The additive 3 is dissolved in deionized water by adding the additive 3 into deionized water, heating and stirring until it melts, and then adding hydrochloric acid to adjust the pH to 2-4 to obtain solution D; The additive 3 is hexadecyltrimethylammonium bromide.

4. The method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material according to claim 1, characterized in that: The aging treatment of the solution E specifically involves aging the solution E at 15-35° C. for 12-24 hours.

5. The method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material according to claim 1, characterized in that: The drying treatment temperature of the reaction product is 60-80°C, and the drying time is 8-10h; the calcination temperature is 500-600°C, the calcination time is 5-6h, and the calcination heating rate is 2-5°C / min.

6. The method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material according to claim 1, characterized in that: The step of dissolving the additive 4 in the solvent 1 specifically comprises dissolving the additive 4 in the solvent 1, stirring at room temperature until dissolved, and then adding hydrochloric acid to adjust the pH to 1-2 to obtain a solution F; The additive 4 is a nonionic surfactant; the solvent 1 is an ethanol aqueous solution.

7. The method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material according to claim 1, characterized in that: After the solution F is added with the carbon source solution, the mass ratio of the additive 4 to the carbon source is 1:(3-7); the carbon source comprises one or more of phenolic resin, polyacrylonitrile and polydopamine; The mass ratio of the pore-forming agent to the template B is 1:(1.8-2.2); the pore-forming agent includes one or more of sodium carbonate, urea, ammonium nitrate and zinc chloride; The solvent 2 is a NaOH solution or a HF solution; The high temperature activation is specifically activated at 750-850°C for 1-2h; The three-dimensional mesoporous carbon material has an ant nest shape.

8. The method for preparing a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material according to claim 1, characterized in that: The chemical vapor deposition of the three-dimensional mesoporous carbon material specifically comprises the following steps: The three-dimensional mesoporous carbon material is evenly spread in a quartz boat, placed in the center of a chemical vapor deposition reaction chamber, and an inert gas is introduced to clean the reaction chamber; A mixed gas 1 is introduced into a chemical vapor deposition reaction chamber to deposit a three-dimensional mesoporous carbon material, wherein the mixed gas 1 includes a silicon source gas; A mixed gas 2 is introduced into the chemical vapor deposition reaction chamber to perform secondary deposition on the three-dimensional mesoporous carbon material, wherein the mixed gas 2 includes a carbon source gas; The three-dimensional mesoporous carbon material after secondary deposition is placed in an inert gas for annealing treatment to obtain a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material.

9. A three-dimensional mesoporous carbon composite silicon-carbon negative electrode material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. Application of a three-dimensional mesoporous carbon composite silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8 in battery materials.

Citation Information

Patent Citations

  • Sulfur-doped three-dimensional hollow porous hemoglobin-like carbon material as well as preparation method and application thereof

    CN113086964A

  • Negative electrode material and preparation method thereof

    CN118630191A

  • Preparation method of silicon-carbon negative electrode material, silicon-carbon negative electrode material and lithium battery

    CN119008907A

  • Modified three-dimensional porous carbon-based silicon-carbon negative electrode material and preparation method thereof

    CN119079990A

  • Nitrogen-doped and carbon matrix-encapsulated silicon-carbon nanofiber composite, method for preparing same, and secondary battery comprising same

    WO2023239046A1